New record for Asia-Pacific of Protoperidinium anomaloplaxum (Peridiniales, Dinophyceae) from Vietnamese waters - Luom, Phan Tan; Lam, Nguyen Ngoc; Hai, Doan Nhu (Academia Journal of Biology, 2020)
Minusculum (Lebour) Balech is one of four subgenera of the genus Protoperidinium Bergh 1881. Only five species of this subgenus have been discovered worldwide, most of which are distributed in cold waters. In this study, Protoperidinium anomaloplaxum (Balech) Balech is reported from Vietnam and thus for the first time from Asia-Pacific waters. This species is illustrated with line drawing, light and scanning electron microscopic photographs and described details of the ornamentation of the thecal plates as well as its geographic distribution.